Pengaruh Proporsi Ekstrak Bumbu Opor dan Maltodekstrin Terhadap Mutu Organoleptik Bumbu Opor Bubuk Instan (International Forum of Researchers and Lecturers, 2025)
Opor is a very popular food, so it is served at almost every celebration. The main key to the deliciousness of opor lies in the spices used, but making opor seasoning is done by mixing many ingredients and spices so that the processing takes a long time. The resulting opor seasoning is also in the form of a paste, so it has a short shelf life and is less practical. This study aims to create instant opor seasoning in powder form so that it is more practical and can be stored for a long time. The method used in this study is an experiment to find a cause-and-effect relationship between the proportion of opor seasoning extract and maltodextrin added to the organoleptic properties of the resulting powdered opor seasoning. Organoleptic tests were conducted on 30 panelists. Based on the panelists' results, the best opor seasoning is produced by mixing 1.5 parts of opor seasoning extract with 1% maltodextrin. This powdered opor seasoning has a fat content of 11.85%, protein 17.63%, and calories 289.5 kcal/100g. The cost required to make powdered opor seasoning per package is IDR 13,000